2, 6-Dichloro-1, 4-benzoquinone formation from chlorination of substituted aromatic antioxidants and its control by pre-ozonation in drinking water treatment plant. (July 2022) - Qiao, Rongrong; Liang, Shiqi; Chen, Chunjing; Xiong, Lilin; Guan, Qiangdong; Wang, Li; Fu, Zhiqiang; Pan, Yang; Liu, Haozhe; Zhu, Jun; Hu, Yechen; Li, Lei; et al.
Abstract: Halobenzoquinones are frequently detected as disinfection by-products in drinking water. Among identified halobenzoquinones, 2, 6-dichloro-1, 4-benzoquinone (2, 6-DCBQ) is particularly toxic and is frequently detected in drinking water. Synthetic aromatic antioxidants discharged to source water may increase the risk of 2, 6-DCBQ formation, as many studies suggest that aromatic compounds are the most likely precursors to 2, 6-DCBQ. Herein, we investigated the formation of 2, 6-DCBQ from chlorination of three model aromatic antioxidants, including 3- tert -butyl-4-hydroxyanisole (BHA), 2, 6-di- tert -butyl-4-methylphenol (BHT) and bis(4- tert -butylphenyl)amine (BBPA). Only BBPA produced 2, 6-DCBQ under chlorination, while chlorination of BHA and BHT formed α, β -unsaturated C4 -dicarbonyl ring-opening products and phenolic compounds. Based on mass balance and intermediate transformation analysis, mechanisms for the formation of 2, 6-DCBQ from BBPA chlorination involved hydrolysis, tert -butyl group cleavage, chlorine substitution, desamination and oxidation. Mitigating aromatic compounds will be an efficient method for 2, 6-DCBQ control, such as pre-ozonation, because the intermediates involved in 2, 6-DCBQ formation were aromatic compounds. Real water samples from two drinking water treatment plants (DWTPs), one with pre-ozonation (DWTP 2) and the other without pre-ozonation (DWTP1), were analyzed. The two DWTPs were built along the Yangtse river in Nanjing city. Raw water parameters from the two DWTPs, including dissolved organic carbon (DOC), UV absorbance at 254 nm (UV254 ) and NH3 –N, indicated the water quality between these sources was similar. Pre-ozonation in DWTP 2 vanished 2, 6-DCBQ in raw water. Concentrations of 2, 6-DCBQ in finished water from DWTP 1 (5.69 ng/L) was higher than concentrations generated from DWTP 2 (1.31 ng/L). These results demonstrate that pre-ozonation, granular activated carbon (GAC) and quartz sand treatments at DWTP 2 remove more 2, 6-DCBQ precursors than the conventional quartz sand and GAC treatments in DWTP 1. These results suggest the pre-ozonation, GAC and quartz sand treatments can help minimize concentrations of 2, 6-DCBQ generated in DWTPs. Graphical abstract: Image 1 Highlights: Bis(4- tert -butylphenyl)amine with large steric hindrance is a precursor for 2, 6-DCBQ. Aromatic intermediates are the key intermediates for 2, 6-DCBQ formation. Ozone decomposed 2, 6-DCBQ in raw water. Ozone, GAC and quartz sand removed 2, 6-DCBQ precursors effectively.